Peers and Exposure to Pornography Are Associated with Adolescent Sexual Behavior: Teman Sebaya dan Paparan Pornografi Berhubungan dengan Perilaku Seksual Remaja - Taqwin; Komile, Vizka Elfanya; Hadriani (Napande: Jurnal Bidan, 2024)
Background: Peer influence and exposure to pornographic media are factors associated with adolescent sexual behavior[PP1]. The results of interviews with twelve students showed that eight students had dated, hugged, and kissed. Four students have watched pornographic videos in class. Objective: to determine the relationship of peers and exposure to pornography with adolescent sexual behavior. Methods: The research method is an analytic survey with a cross-sectional design. The study population was all students at one of the junior high schools in Sigi Regency, Central Sulawesi. A sample of 74 respondents was taken using a simple random technique. Independent variables were peers and exposure to pornography. The dependent variable was adolescent sexual behavior. The data collection instrument used a questionnaire. Data analysis used a chi-square test. Results:  The results showed that the percentage of respondents with risky sexual behavior was 66.2%. The results also showed that out of 74 respondents, peers who supported risky sexual behavior were 47 respondents (63.5%). Respondents who were exposed to pornography were 42 (56.8%). The statistical test results showed that the ρ value of peers and exposure to pornography with adolescent sexual behavior =0.0005 (<0.05). Conclusion: The study concludes that peers and exposure to pornography are associated with sexual behavior. It is expected that parents and teachers can educate students about sexual behavior.